Inhibitory Activity of Sea Grapes (Caulerpa racemosa) Against the Growth of Propionibacterium acnes - Yessie K. Lengkey; Indri J. Kereh; Sonny D. Untu; Margaretha S. Ginting; Ferdy A. Karauwan; Selvana S. Tulandi; Adolfina Sumagando (FMIPA UKIT, 2025)
This study aimed to determine the inhibitory activity of sea grapes (Caulerpa racemosa) against the growth of Propionibacterium acnes, a bacterium that can cause acne on human skin. Sea grapes contain bioactive compounds such as flavonoids and alkaloids which may act as natural antibacterial agents. This research was conducted experimentally in the laboratory using the agar diffusion method with paper discs. The sea grape sample was extracted by maceration using 96% ethanol and tested at concentrations of 100, 200, 300, and 400 µg/disc. Distilled water was used as a negative control. The results showed that the extract was able to inhibit the growth of Propionibacterium acnes, with inhibition zone diameters ranging from 33.9 to 41.2 mm. The largest inhibition zone was found at the concentration of 400 µg/disc. In conclusion, sea grapes (Caulerpa racemosa) have very strong antibacterial activity against Propionibacterium acnes and have potential as a natural antibacterial source.